Tunable-Deformed Graphene Layers for Actuation - Wang, Jiaqi; Xiao, Yukun; Cecen, Volkan; Shao, Changxiang; Zhao, Yang; Qu, Liangti (Frontiers in Chemistry, 2019)
Benefiting from unique planar structure, high flexibility, splendid thermal and electric properties, graphene as a crucial component has been widely applied into smart materials and multi-stimulus responsive actuators. Moreover, the graphene with features of easy processing and modification can be decorated with various functional groups through covalent or non-covalent bond, which is promising in conversion of environmental energy from single and/or multi-stimuli to mechanical energy. In this review, we present the actuating behaviors of graphene regulated by chemical bonds or intermolecular forces under multi-stimulus, and summarize the recent advances on account of the unique nanostructures in various actuation circumstances such as thermal, humidity, electrochemical, electro-/photo-thermal, and other stimuli.